INTEGRATED METHODS FOR DELINEATING GROUNDWATER RESOURCE IN ADO-EKITI, SOUTHWESTERN NIGERIA (2017)
Potable water supply in Ado-Ekiti is inadequate resulting in increased demand for groundwater in the metropolis. Geologically, Ado-Ekiti is underlain by hydrogeologically challenging crystalline basement rocks whose hydraulic properties are characterised by extreme variations over short distances. Prospective groundwater zones are poorly defined in the hard rock terrain. A thorough and definitive evaluation of the overall groundwater resource in such terrain is imperative. This study was therefore designed to use integrated investigations comprising Hydro-geophysics, Remote Sensing and Physicochemistry, in delineating areas suitable for sustainable groundwater development. Landsat imageries were used for landuse and landcover mapping, while lineament analysis was used for groundwater prospecting. Shuttle Radar Topographic Mission Digital Elevation Model (SRTM DEM) was used for drainage network extraction, slope and geomorphological analysis. Well inventory data were obtained from 108 wells with physicochemical analysis of the water samples. One hundred and thirty three Vertical Electrical Soundings (VES) were carried out to generate geoelectric parameters including the Dar Zarrouk Parameters. Application of Geographical Information System (GIS) enabled the preparation of various thematic maps which were analysed in terms of hydrogeologic importance. The thematic maps of the extracted features were re-classified for integration using appropriate software. The groundwater potential maps generated were validated against the existing groundwater yield data. Well yield data were superimposed on the groundwater potential maps. Data were analysed using descriptive method. The light vegetation and bare soil area cover was 110.9 km2, with the rock outcrops covering a total area of 14.9 km2. Hills, pediments, pediplains, alluvium and valley fills were the hydrogeomorphic units delineated. The lineaments showed predominantly, NNW-SSE, ENE-WSW and NNE-SSW orientations and subsidiary NW-SE and W-E trends. The weathered/fractured basement layer revealed a range of resistivity value of 16.5 Ωm – 1214.0 Ωm with thickness varying from 0.2 m to 53.2 m. The overburden thickness, coefficient of anisotropy and groundwater head had values varying from 1.0 m - 63.2 m, 1.0 – 3.0 and 292.2 – 460.4 m amsl, respectively. Groundwater potential maps generated from remote sensing – GIS and VES – GIS gave highest correlation with borehole yield data of 56.7% and 60%, respectively. Integration of the thematic layers of bedrock resistivity, weathered basement iii resistivity, overburden thickness, lineament density, geology, geomorphology and anisotropy yielded a groundwater potential map with a marked improvement of 73.3% correlation. The area was classified into very low, low, medium and high groundwater potential zones covering 61.4 km2, 118.9 km2, 38.2 km2 and 16.8 km2, respectively. Valley fills/basement depressions and major groundwater recharge/discharge zones were delineated as groundwater pockets with the flow approximately lying along the NW-SE direction. The integrated approach has proven to be efficient and effective for delineation of groundwater potential zones in Ado –Ekiti. This approach will minimize the time and cost for identifying groundwater potential zones and suitable recharge structures in basement terrains. Keywords: Basement complex, Geomorphology, Groundwater potential, Lineament extraction Word count: 461